2021
DOI: 10.1016/j.neuroimage.2021.118286
|View full text |Cite
|
Sign up to set email alerts
|

Heritable functional architecture in human visual cortex

Abstract: How much of the functional organization of our visual system is inherited? Here we tested the heritability of retinotopic maps in human visual cortex using functional magnetic resonance imaging. We demonstrate that retinotopic organization shows a closer correspondence in monozygotic (MZ) compared to dizygotic (DZ) twin pairs, suggesting a partial genetic determination. Using population receptive field (pRF) analysis to examine the preferred spatial location and selectivity of these neuronal populations, we es… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…These findings regarding the heritability of visual cortex confirm reports from another recently published paper (Alvarez et al, 2021), which evaluated an independent sample of approximately half as many twins as used here. Alvarez et al .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings regarding the heritability of visual cortex confirm reports from another recently published paper (Alvarez et al, 2021), which evaluated an independent sample of approximately half as many twins as used here. Alvarez et al .…”
Section: Discussionsupporting
confidence: 90%
“…These findings regarding the heritability of visual cortex confirm reports from another recently published paper (Alvarez et al, 2021), which evaluated an independent sample of approximately half as many twins as used here. Alvarez et al examined the V1-V3 organization of 36 twin pairs and found both greater visual area overlap in MZ than DZ twins and higher correlations of cortical properties (as in Figs.…”
Section: Mz Twins' Retinotopic Maps Are More Similar Than Those Of Dz...supporting
confidence: 90%
See 1 more Smart Citation
“…Previous work examining the visual cortex in the context of twins and heritability has found some evidence of genetic control. The variance of resting-state fluctuations within the visual cortex has a strong genetic component ( Yang et al, 2016 ), and the surface areas of V1–V3 are more correlated for monozygotic than dizygotic twins ( Alvarez et al, 2021 ; Benson et al, 2021b ). Interestingly, our analysis of the asymmetries of twin pairs in the dataset demonstrated differences between HVA and VMA.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of interindividual variability in determining brain development and (dys)function, the origins of neural variability remain unclear. Heritability has been shown to account for a high percentage of variance ( Polk et al, 2007 ; Park et al, 2012b ; Yang et al, 2016 ; Ge et al, 2017 ; Reineberg et al, 2020 ; Alvarez et al, 2021 ) but does not explain the full range of individual differences. One large source of variability, the effects of environmental factors such as sensory experience, remains particularly unclear.…”
Section: Introductionmentioning
confidence: 99%